'In the mind's eye': A cognitive linguistic re-construction of WD Snodgrass' 'Matisse: The Red Studio'. (May 2016) - Panagiotidou, Maria-Eirini
Although ekphrastic poetry has always been a popular poetic genre, the twentieth century saw a profusion in the production of literary texts that describe art objects. Ekphrastic criticism is abundant with critical discussions raising questions concerning aesthetics, the value of artistic creations, and the nature of representation. However, these discussions rarely consider the experience of reading an ekphrastic poem or account for readers' responses to ekphrastic texts. The present paper uses the tools and methodology of cognitive poetics to examine how WD Snodgrass' ekphrastic poem 'Matisse: The Red Studio' may be mentally reconstructed. The analysis focuses on figure–ground relations and the psychological notion of attention to explore how textual cues are brought together to create a representation of the painting described in the poem. It examines the use of particular lexical items that denote colors, forms, and textures as they become available for processing into objects. While addressing Snodgrass' questions concerning the ownership of art objects and the notion of 'still movement', it also illustrates the ability of cognitive poetics to account for reader responses to ekphrastic poems in a way that complements and expands on trends in linguistics and literary criticism.